2004
DOI: 10.1148/radiol.2303021183
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Radiation Therapy in Liver Tissue in a Pig Model: Monitoring with Dual-Modality PET/CT

Abstract: The morphologic and functional changes due to IORT in liver tissue can be accurately monitored with dual-modality PET/CT. By enabling the integration of functional and morphologic data, PET/CT may have an important role in monitoring radiation treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Antoch et al . [ 17 ] reported their findings of the utility of PET/CT in the assessment of liver tissue after intraoperative radiation therapy in a pig model. They found that PET/CT showed a decrease in the uptake of FDG in the irradiated field at 2 and at 4 weeks following completion of intraoperative therapy using 20 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…Antoch et al . [ 17 ] reported their findings of the utility of PET/CT in the assessment of liver tissue after intraoperative radiation therapy in a pig model. They found that PET/CT showed a decrease in the uptake of FDG in the irradiated field at 2 and at 4 weeks following completion of intraoperative therapy using 20 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…The typical doses applied ranged from 15 to 30 Gy with reference to the tumor margin. The brachytherapy technique generally leads to a high dose inhomogeneity in the target volume [14][15][16][17][18] . However, the intraoperative approach has some drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…The threshold dose for wholeliver irradiation without chemotherapy is supposed to be 20 -30 Gy (21,22). In patients who undergo combined radiation therapy and chemotherapy or combined radiation therapy and immunotherapy, the risk for development of radiation-induced liver disease is higher (23,24).…”
mentioning
confidence: 99%